Effects of Oat Bran Addition on the Growth Performance and Intestinal Health of Nile Tilapia (Oreochromis niloticus) Exposed to Copper Ions - Chunze Guo; Yingchao Zhang; Xuekai Wang; Kuikui Ni; Qiang Hao; Zhen Zhang; Zhigang Zhou; Fuyu Yang (Aquaculture Nutrition)
This study investigated the effects of the oat bran addition on the growth performance and intestinal health of Nile tilapia (Oreochromis niloticus) exposed to copper ions. Four groups of diets containing 0%, 5%, 10%, and 20% oat bran were fed to Nile tilapia for four weeks. The results showed that oat bran had a dose-dependent effect on the growth performance of Nile tilapia. The addition of oat bran can increase the relative abundance of Delftia, which is capable of degrading heavy metals in the intestinal tract and alleviating the intestinal damage caused by copper ion stress. Compared to the control group, the 5% oat bran group had an increased intestinal antioxidant capacity. The relative gene expression of proinflammatory factors (NF-κB, IL-1β) was significantly downregulated in the 5% oat bran group (P<0.05), and the relative gene expression of anti-inflammatory factors (TGF-β), HIF-1α, occludin, and claudin was significantly upregulated (P<0.05). In conclusion, we suggest that 5% oat bran should be added to the diet to improve the growth performance of Nile tilapia and alleviate the negative effects of copper ion stress on intestinal health.